2013
DOI: 10.2319/021113-124.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cephalograms on decisions for early orthodontic treatment

Abstract: Objective: To assess the extent to which cephalograms modify therapeutic decisions related to early orthodontic treatment. Materials and Methods: Diagnostic records of six patients requiring early treatment were digitized for this purpose. A total of 234 orthodontists were then asked to select therapeutic measures on a treatment-planning sheet at two different times (T1 and T2). Three groups of orthodontists were formed and were provided with case-specific records either including or not including cephalograms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Exclusion of the LCR did not influence the orthodontic treatment decision of extraction, which is rather an irreversible decision. This recognition corresponds with previous studies [ 6 , 11 , 14 , 16 ]. The contribution of the LCR to orthodontic decision making, as one of the essential orthodontic diagnostic materials might be questionable [ 5 , 6 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Exclusion of the LCR did not influence the orthodontic treatment decision of extraction, which is rather an irreversible decision. This recognition corresponds with previous studies [ 6 , 11 , 14 , 16 ]. The contribution of the LCR to orthodontic decision making, as one of the essential orthodontic diagnostic materials might be questionable [ 5 , 6 ].…”
Section: Discussionsupporting
confidence: 93%
“…LCR seemed to have a higher impact on diagnosis than on treatment planning [ 6 ]. On the contrary, it was reported that clinical examination and dental casts might be sufficiently informative to estimate future skeletal development under certain circumstances [ 6 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study revealed limited disagreements for treatment modality preferences and no disagreement for extraction decision when the LCRs were omitted. This is in accordance with previous studies questioning the benefit of routine LCR prescription (4)(5)(6)(7). This outcome may lead us to a possible assumption that the routine prescription of the three sets of LCRs may not be due to actual need but as a result of the orthodontist's training.…”
Section: Discussionsupporting
confidence: 74%
“…It provides linear and angular associations for sagittal and vertical levels of facial bone structures but does not comprise the transversal dimension or function -in other words, the third dimension (1,2). This drawback has led to the questioning of routine prescription and interpretation of LCR regarding its influence on specific malocclusions (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the methods that use radiographs have the advantage of measuring unerupted teeth, and provide more accurate results, but the patient is exposed to ionizing radiation, and it requires additional radiographs, which implicates financial costs 12 . Huckaba 9 (1964) developed a method for overcoming the effect of radiographic distortions while measuring the permanent canines and premolars MD width, using an equation relating the measures of erupted teeth to their radiographic images in order to obtain the proportional dimensions of unerupted teeth, as follows:…”
mentioning
confidence: 99%